Floral biology, morphology and ecological niche modelling of Caraipa grandifolia (Calophyllaceae), an important Amazonian floodplain tree - Versieux, Leonardo de Melo; Acosta, André Luis; Jordão, Alexandre Luis; Zidko, Alexsandro; Maia, Ulysses Madureira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The present work aims to investigate the floral biology and morphology of one member of the Calophyllaceae (or Clusiaceae sensu lato), Caraipa grandifolia in the Caxiuanã National Forest, in the eastern Brazilian Amazon and aims to identify the bioclimatic affinities of this species, providing insights about its environmental requirements and mapping its potential distribution, given the paucity of data about flood-tolerant trees. Nine flowering individuals were located along a 2 km stretch of the Anapu river, and were visited by eleven different species (some of which are potential pollinators) including cockroaches, bees, ants, and wasps. Flower anthesis occurred between 05:00 and 07:30. The flowers are odourous, and osmophores were observed along the petals and also on top of each individual anther. The main reward collected by bees was pollen and an oily resin/scent produced by anther glands, while four different ant species collected nectar in inconspicuous extranuptial nectaries along the flower pedicel, a morphological feature previously unreported for the genus. Caraipa grandifolia is considered to be an important tree species in the flooded forest ecosystems given the number of interactions with which it is involved and its potentially wide distribution indicated by our modelling.
Keywords: Clusiaceae; Dictyoptera; Igapó